Graphene synthesized by chemical vapor deposition as a hydrogen isotope permeation barrier. (May 2021) - Young, Katherine T.; Smith, Colter; Krentz, Timothy M.; Hitchcock, Dale A.; Vogel, Eric M.
Abstract: This work presents the results of gas concentration driven deuterium permeation experiments through chemical vapor deposited graphene on copper. Since the graphene is synthesized directly onto the copper, the permeation experiments are able to be performed over a large area (16.62 mm 2 ) without the detrimental impact of transfer-induced tears and holes. Thus, permeation through intrinsic defects of the graphene are probed. The graphene-coated copper shows a reduction in permeation by a factor of ∼28 compared to copper alone. The permeation results are modeled with a composite permeation model. The permeation of copper alone is shown to be proportional to the square root of pressure, whereas the permeation through graphene samples is proportional to pressure. The graphene permeance follows an Arrhenius behavior. The room temperature pore permeation coefficients for the small and large grain graphene samples are ∼7.0 × 10 −28 ±5.0 × 10 −28 and ∼1.9 × 10 −27 ±1.4 × 10 −27  mol s −1  MPa −1, respectively. These results suggest that grain boundaries are not the main diffusion pathways, and instead other intrinsic defects in the graphene demonstrate less resistance to permeation. This study advances the fundamental understanding of the intrinsic permeation of chemical vapor deposited graphene, as well as the use of graphene in hydrogen isotope permeation barrier applications. Graphical abstract: Image 1